Loss of cell polarity regulated by PTEN/Cdc42 enrolled in the process of Hepatopulmonary Syndrome. Issue 8 (29th May 2019) - Gao, Jing; Yu, Hongfu; Bai, Xuehong; Liu, Chang; Chen, Lin; Belguise, Karine; Wang, Xiaobo; Lu, Kaizhi; Hu, Zhiyong; Yi, Bin
Abstract: One central factor in hepatopulmonary syndrome (HPS) pathogenesis is pulmonary vascular remodelling (PVR) which involves dysregulation of proliferation and migration in pulmonary microvascular endothelial cells (PMVECs). Growing evidence suggests that Apical/basolateral polarity plays an important role in cell proliferation, migration, adhesion and differentiation. In this study, we explored whether cell polarity is involved and critical in experimental HPS rats that are induced by common bile duct ligation (CBDL). Cell polarity related proteins were analysed in CBDL rats lung and PMVECs under the HPS serum stimulation by immunofluorescence assay. Cdc42/PTEN activity, cell proliferation and migration and Annexin A2 (AX2) in PMVECs were determined, respectively. Cell polarity related proteins, lost their specialized luminal localization in PMVECs of the CBDL rat. The loss of cell polarity was induced by abnormal activity of Cdc42, which was strongly enhanced by the interaction between p ‐PTEN and Annexin A2 in PMVECs, after treatment with serum from CBDL rats. It led to over‐proliferation and high migration ability of PMVECs. Down‐regulation of PTEN‐Cdc42 activity in PMVECs restored cell polarity and thus reduced their ability of migration and proliferation. Our study suggested that the loss of cell polarity plays a critical role in the pathogenesis of HPS‐associated PVR and may become a potentially effective therapeutic target.